Analisis Pengaruh Sifat Kebasahan (Wettability) Terhadap Tekanan Kapiler dan Sifat Kelistrikan pada Batuan Formasi X - Faiqotul Hikmah; Hadziqul Abror; Eriska Eklezia Dwi Saputri (Jurnal Migasian, 2025)
This research was carried out with the aim of determining the effect of wettability on depth pressure and electrical properties in X formation rocks. The samples used in the research were 6 samples with a diameter of 1.5 cm. Testing the wettability properties using the Amott method with the Amott Cell, testing the glass pressure using a porous plate and testing the electrical properties using a resistivity meter. Testing for the wettability of THV samples in the Amott Harvey Index is in the range -0.8901 to -0.9825. Glass pressure tests were carried out to represent the height of the transition zone in the reservoir and produced Swirr values in the range of 20% to 31% of the pore volume. The saturation of the air sample in THV-2 is stable at a pressure of 100 psi and the THV-5 sample is stable at a pressure of 200 psi. In testing the electrical properties of rocks, the formation factor curve aims to obtain the cementation factor value (m) and the resistivity index curve to obtain the saturation exponent value (n). The m value obtained is 1.73 and the n value is 3.10. The conclusion from this research is that Formation Representation of aquarium pressure against the height of the transition zone results in rocks that have strong oil wet properties will have a shorter transition zone while rocks that have weaker oil wet properties will have a longer transition zone. This research did not find a clear relationship between wettability and resistivity.